A STUDY AND ANALYSIS OF THE PROMOTION OF A GROWTH MINDSET IN EDUCATIONAL INSTITUTION ADMINITRATION: A CASE STUDY OF THE THUNGKHANAN WITTAYA SCHOOL, SOI DAODISTRICT, CHANTHABURI PROVINCE - Sittisuwan, Rawiwan; Nilkote, Reongwit; Boonloy, Waiwoot (Journal of MCU Nakhondhat, 2024)
The objectives of this research were to : 1) study the context and promotion of a growth mindset in the management of educational institutions at Thung Khanan Wittaya School, Soi Dao District, Chanthaburi Province 2) analysis of the potential of promoting a growth mindset in school administration at Thung Khanan Wittaya School, and 3) proposing guidelines for promoting a growth mindset in school administration at Thung Khanan Wittaya School under the secondary educational service area office chanthaburi, trat. It is qualitative research. Collect data through in - depth interviews, discussions, and participatory observations. The tools are interview forms. interview 15 key informants and focus group discussions. Six key informants were purposively selected. The sample selection criteria were 1) being personnel in Thungkanan Wittaya School for at least 3 years, 2) participating in school activities for 80 percent, and 3) being willing to provide information throughout the research. Participants in focus groups and in-depth interviews were different groups. Content synthesis, triangulation, and descriptive presentation. The results of the research showed that: 1) Promoting an integrated growth mindset through education management through activities, adhering to school education standards as the main goals, and developing quality in accordance with the vision, mission, objectives, quality development strategies of education management, and reflecting the school’s identity, 2) The school has integrated a growth mindset based on the educational standards, policies, strategies, and development plans of Chanthaburi Trat Secondary Education Area by integrating in 6 strategic areas, and 3) The development approach consists of 3 parts: there must be a development approach to promote a growth mindset in school management, an action mechanism to promote a growth mindset.